Case Report: Rehabilitation After Platelet-Rich Growth Factors’ Intra-Articular Injections for Knee Osteoarthritis: Two Case Reports of a Home-Based Protocol - Negrini, Francesco; De Lucia, Francesco; Negrini, Stefano; Tornese, Davide; Facchini, Francesca; Vecchio, Michele; de Girolamo, Laura (Frontiers in Pharmacology, 2021)
Knee osteoarthritis (KOA) is a chronic progressive disease that can cause pain, functional impairment, and ultimately disability. A novel and promising therapeutic approach to KOA is the so-called regenerative medicine, a set of procedures designed to harness tissue regenerative capacity and optimise functional recovery. Increasing evidence point out that Platelet Rich Plasma (PRP) intra-articular injections can decrease pain and improve functional abilities in KOA patients. In the present case reports we analyse two patients that were treated with PRP injections coupled with a post-treatment home-based rehabilitation program. The two patients were selected to represent two different populations: patient 1 was a 85-year-old with severe impairment of functional abilities, while patients 2 was a younger (59 years old) and more active patients. The protocol consisted in a series of exercise to be performed at home, during the five days following PRP injection for two consecutive weeks (10 days in total). The exercises were designed to reduce the inflammation after the injection, enhance the proprioceptive control of the treated lower limb and strengthen hip and knee flexors and extensors, mainly by isometric work. Results were evaluated at two timepoints: before and two months after the first PRP injection. Outcome considered were Visual Analogue Scale for PAIN, EuroQol 5 Dimensions Questionnaire, Tegner Activity Scale for functioning, and Knee injury and osteoarthritis outcome score (KOOS). Both patients did not report any side effect from the treatment. Patient 1 improved drastically at the two months follow-up as far as pain and functional abilities are concerned. Patient 2 improvement were less evident, probably due to the higher starting point in both pain and functionality. Overall, the developed program seemed safe and was tolerated by the patients analyzed in the study, who performed it with good compliance.